Key Informants' Perspectives: Management Commitment, Training, and Worker Participation in the Prevention of Musculoskeletal Disorders. Issue 3 (2nd October 2017) - Yazdani, Amin; Hilbrecht, Margo; Imbeau, Daniel; Bigelow, Philip; Neumann, W. Patrick; Pagell, Mark; Wells, Richard
Abstract : OCCUPATIONAL APPLICATIONS To implement effective musculoskeletal disorder (MSD) prevention programs in organizations, there needs to be commitment from top and middle management, ongoing worker participation, and effective training and education. This study addresses practical solutions for the successful execution of these elements with businesses and organizations in mind. The specific structures, concerns, and unique operating environments of organizations are considered to put together practical advice by experts in the field. Conclusions of the study reveal best practices, essential components, and ideas to improve and employ these elements to improve current MSD prevention strategies in the workplace. TECHNICAL ABSTRACT Background : Prevention of MSD in the workplace presents many challenges. There are high costs to the organization, worker, and society associated with these occupational injuries. Therefore, it is important to identify which methods and approaches companies should use to successfully tackle this issue. Purpose : This study sought to determine which elements—in relation to management commitment, worker participation, and training—are effective for successful MSD prevention. Methods : Twenty-three key informants, including consultants, managers, researchers, union representatives, and policy makers, all experienced in health and safety and MSD prevention, were consulted using a structured interview format. Data were analyzed based on a thematic analysis approach. Results : Information was gathered for the definition of management commitment, its importance, methods for improvement, and examples of good practices to achieve management support. Key informants also discussed the importance of worker participation for effective MSD prevention, success stories, and how to encourage effective and sustainable participation. Lastly, informants shared insights into optimal training programs, methods, and contents. Results of the interviews with key informants revealed that crucial aspects of effective MSD prevention programs are training and education of managers and workers on MSD prevention, commitment from top and middle management, and worker participation in the early stages on plans and interventions. It was emphasized that a common, consistent language needs to be used throughout any programs, research, training, and organization-wide initiatives. Promoting the business case for MSD prevention was also recommended to gain management buy-in. Conclusions : Results of this study suggest that integrating MSD prevention activities into key elements of a broader management framework can positively and effectively influence the success of MSD prevention initiatives.